Dairy cow ownership and child nutritional status in Kenya - Nicholson, C.; Mwangi, L.; Staal, Steven J.; Thornton, Philip K. (American Agricultural Economics Association, 2003)
This study examines the hypothesis that dairy cow ownership improves child nutritional status. Using household data from coastal and highland Kenya, three econometric model formulations are estimated. Positive impacts on chronic malnutrition are observed for coastal Kenya. No negative effects on acute or chronic malnutrition are found for either region.